Implementation of Information System and Software Quality Testing in Company Operational Applications Based on ISO/IEC 25010: Case Study: PT Snapdev Digital Indonesia - Muhammad Alief Kemal; Salsa Apriliani Saka; Chairul Anwar (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
Information system quality testing is a critical factor in supporting the effectiveness and efficiency of corporate business operations. This study aims to implement and evaluate software quality based on the ISO/IEC 25010 international standard within the E-Office (Digital Archive) operational applications of PT Snapdev Digital Indonesia. Quality testing is comprehensively conducted across eight main characteristics: Functional Suitability, Performance Efficiency, Compatibility, Usability, Reliability, Security, Maintainability, and Portability. The research methodology employs a quantitative descriptive approach using a structured questionnaire distributed to active users. Through purposive sampling, a final sample size of 27 active respondents was established. The empirical results show that the percentage scores for each quality aspect range from 80.00% to 86.67%, which demonstrates that the system successfully satisfies the standard software quality requirements. The overall average score of 83.56% places the system quality in the